(untitled) (Applied Biological Research, 2023)
An efficient and reproducible protocol is required to achieve high frequency transformation from transformed calli. In this paper, high frequency plant regeneration from mature embryo-derived embryogenic calli of recalcitrant indica rice cultivars (‘Khandagiri’, ‘Sahbhagidhan’ and ‘Mandakini’) is reported. Maximum frequency of embryogenic and nodular callus (73.5%) followed by plant regeneration (88.5%) was obtained in cv. ‘Khandairi’. Further, ‘Sahbhagidhan’ (82.3%) and ‘N22 Sel’ (75.3%) showed higher organogenic plantlet regeneration than ‘Mandakini’ (70.8%), but reverse was the case for somatic embryogenic plant regeneration. Rice cv. ‘Annada’ and ‘Vandana’ exhibited poor organogenic and somatic embryogenic callusing and plantlet regeneration response. Therefore, organogenic and somatic embryogenic plant regeneration have their own genetic basis and these two phenomena might be under separate genetic control in various genotypes. The present high throughput plant regeneration system can be amenable for genetic improvement through in vitro mutagenesis and Agrobacterium-mediated genetic transformation in upland rice.